2021
DOI: 10.3390/cancers13071725
|View full text |Cite
|
Sign up to set email alerts
|

The Yin and Yang of Discoidin Domain Receptors (DDRs): Implications in Tumor Growth and Metastasis Development

Abstract: The tumor microenvironment is a complex structure composed of the extracellular matrix (ECM) and nontumoral cells (notably cancer-associated fibroblasts (CAFs) and immune cells). Collagens are the main components of the ECM and they are extensively remodeled during tumor progression. Some collagens are ligands for the discoidin domain receptor tyrosine kinases, DDR1 and DDR2. DDRs are involved in different stages of tumor development and metastasis formation. In this review, we present the different roles of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 157 publications
(243 reference statements)
0
26
0
Order By: Relevance
“…As a key component of the tumor extracellular matrix, type I collagen shows high density and distorted architecture in malignant cancer, linking it to tumor formation and metastasis [ 83 ]. Therefore, the discovery of DDRs as collagen receptors represents a new target in the regulation of tumor progression [ 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Role Of Ddr In Cancermentioning
confidence: 99%
“…As a key component of the tumor extracellular matrix, type I collagen shows high density and distorted architecture in malignant cancer, linking it to tumor formation and metastasis [ 83 ]. Therefore, the discovery of DDRs as collagen receptors represents a new target in the regulation of tumor progression [ 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Role Of Ddr In Cancermentioning
confidence: 99%
“…A similar pro-apoptotic function of DDR1 was demonstrated in HT-29 colon carcinoma cells encapsulated in 3D COL1 (Le et al, 2020). These observations contrast with the classical concept that DDR1 expression in cancer cells is associated with an increased cell survival and proliferation (for review, see Majo and Auguste, 2021). Interestingly, a reduction in DDR1 mRNA levels was shown in most middle-to high-grade human breast carcinomas compared with normal mammary tissues (Neuhaus et al, 2011).…”
mentioning
confidence: 79%
“…The same group has later shown that in an in-vivo mouse model of breast carcinoma, inhibition of DDR2 by the small-molecule allosteric inhibitor of DDR2 extracellular domain (WRG-28), was able to disrupt DDR2/COL1 interaction, thus leading to a decrease in SNAIL1 activity and an inhibition of DDR2 pro-metastatic effect ( Grither and Longmore, 2018 ). Interestingly, in those papers, DDR2 signaling was induced during EMT, but was not necessary for the induction of EMT ( Zhang et al, 2013 ; Majo and Auguste, 2021 ). Together, these data suggest a switch of DDRs expression during EMT.…”
Section: Collagen Remodeling Regulates Ddr1 Signaling and Collagen-induced Apoptosismentioning
confidence: 98%
See 1 more Smart Citation
“…Dysregulation of DDR1 and DDR2 has been observed in many solid tumor types (including breast, ovarian, liver, gastric, colorectal, lung, brain, cervical, hematological, head and neck, melanoma, bladder, kidney, and prostate), and can be associated with aggressive metastatic tumors (including breast and ovarian) and a poor prognosis (Gadiya and Chakraborty, 2018; Orgel and Madhurapantula (2019). Yeh et al, 2019;Lafitte et al, 2020;Majo and Auguste, 2021). As discussed above, DDR dysregulation leads to many alterations which influence tumor development, pathology, and key clinical characteristics (key altered clinicopathological features being treatment response and prognosis) (Borza and Pozzi, 2014;Mehta et al, 2021).…”
Section: Discoidin Domain Receptor Tyrosine Kinase Dysregulation In Cancermentioning
confidence: 99%